2019
DOI: 10.1016/j.neuron.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

SynGO: An Evidence-Based, Expert-Curated Knowledge Base for the Synapse

Abstract: Graphical Abstract Highlights d SynGO is a public knowledge base and online analysis platform for synapse research d SynGO has annotated 1,112 genes with synaptic localization and/or function d SynGO genes are exceptionally large, well conserved, and intolerant to mutations d SynGO genes are strongly enriched among genes associated with brain disorders Correspondence guus.smit@cncr.vu.nl (A.B.S.), matthijs@cncr.vu.nl (M.V.) In BriefThe SynGO consortium presents a framework to annotate synaptic protein location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
734
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 691 publications
(803 citation statements)
references
References 84 publications
11
734
0
Order By: Relevance
“…Enrichment analyses showed the postsynaptic density as the main altered GO term and the immune response as dominant pathways (supplementary figure 1). To further characterize and confirm the synaptic involvement, we used the SynGO database, which provides an expert-curated resource for synapse function and gene enrichment analysis(23). This analysis confirmed the enrichment of postsynaptic components in our list of differentially expressed isoforms (supplementary…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Enrichment analyses showed the postsynaptic density as the main altered GO term and the immune response as dominant pathways (supplementary figure 1). To further characterize and confirm the synaptic involvement, we used the SynGO database, which provides an expert-curated resource for synapse function and gene enrichment analysis(23). This analysis confirmed the enrichment of postsynaptic components in our list of differentially expressed isoforms (supplementary…”
mentioning
confidence: 54%
“…Gene ontology and KEGG pathway enrichment analyses were applied using default parameters (minimum overlap=3, p-value cutoff=0.01 and minimum enrichment=1.5) in Metascape 3.0 (22) (http://metascape.org). Synaptic enrichment analyses were also run using the web server SynGO (https://www.syngoportal.org/), which provides an expert-curated resource for synapse function and gene enrichment analysis (23).…”
Section: Data Processingmentioning
confidence: 99%
“…To investigate the significance of these modules further, we sought to identify whether the enrichment of genes relating to synaptic transmission was driven by genes involved in postsynaptic as compared to pre-synaptic structures. To address this question, we checked for enrichment of genes that have been reliably associated with a specific synaptic structure using the recently released SynGO database (Koopmans et al, 2019). This demonstrated significant enrichment of genes associated with both presynaptic and postsynaptic structures amongst those contained within all four modules of interest (namely the substantia nigra "cyan", putamen "cyan", frontal cortex "lightyellow" and white matter "blue" modules).…”
Section: Resultsmentioning
confidence: 99%
“…Gene modules were functionally annotated with gProfileR R package using Gene Ontology (GO) database without Electronic Inferred Annotations (EIA) and accounting for multiple testing with gSCS (Reimand et al, 2007). Additional functional annotations for modules of interest were generated using the web server SynGO (https://www.syngoportal.org/), which provides an expert-curated resource for synapse function and gene enrichment analysis (Koopmans et al, 2019). All gene set enrichment analyses were performed using default 1 0 settings, with no annotation filters applied and a minimum gene count of three for ontology terms to be included in the overrepresentation analysis.…”
Section: Weighted Gene Co-expression Analysis (Wgcna)mentioning
confidence: 99%
“…7d. Five out of 10 clusters have relationship to the synapse (protein localization in synapse, synaptic vesicle transport, dendrite spine morphogenesis, transport along microtubule, junction substrate adhesion), thus we performed enrichment analysis using expert-curated and evidencebased synaptic gene ontology (SynGO) 35 . This revealed that DETs engaged by SD (Ctrl/S vs Ctrl/SD) are highly enriched in synaptic localizations, particularly in postsynapse ( Fig.…”
Section: Neuronal Translatome Regulation By Fxr1 During Sleep Deprivamentioning
confidence: 99%